The Contribution of Islamic Economics to the Equitable Distribution of National Income - Azhari Syahfutra Harahap; Uswatun Hasanah (International Journal of Community Service Implementation, 2026)
Income distribution inequality remains one of the major challenges in economic development, contributing to poverty, social disparities, and economic instability. Although economic growth continues to increase, achieving equitable welfare distribution remains a significant concern, particularly in developing countries such as Indonesia. In this context, Islamic economics offers a distributional framework based on the principles of justice, balance, and social responsibility through various distributive economic instruments. This study aims to analyze the contribution of Islamic economics to the equitable distribution of national income and to examine the role of Islamic economic instruments in reducing economic inequality within society. This research employs a library research method with a descriptive qualitative approach. Data were collected from various sources, including books, scientific journals, previous studies, official documents, and regulations related to Islamic economics. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that Islamic economics significantly contributes to equitable income distribution through instruments such as zakat, infaq, sadaqah, productive waqf, and profit-sharing mechanisms. These instruments function as wealth redistribution mechanisms capable of reducing economic disparities, improving social welfare, expanding access to economic resources, and promoting inclusive and sustainable economic development. Furthermore, the profit-sharing system in Islamic economics provides a fairer alternative to the interest-based system by emphasizing proportional risk and profit sharing. This study concludes that optimizing Islamic economic instruments can serve as an effective strategy for achieving a more equitable national income distribution and supporting comprehensive social welfare.